Obesity Management - a Clinician’s Perspective: Obesity management - Polovina, Snežana; Šumarac-Dumanović, Mirjana; Micić, Dragan (Archives of Pharmacy, 2024)
The global epidemic of obesity has affected almost every country in the world, causing an enormous social and health burden. Although many counter-measures have been introduced against this epidemic, obesity is still on the rise. An important step in this area was made when obesity was classified as a disease. The recognition of obesity as a disease enables governments and state agencies to develop their own plans to curb the obesity epidemic. Obesity has been recognized as a problem from ancient times, and different measures have been suggested as solutions. Modern management of obesity is currently based on the following therapeutic principles: diet, exercise, psychological support, pharmacological treatment, and bariatric surgery. The history of pharmaceutical treatment is rather long and full of withdrawals of the drugs due to various reasons. New perspectives and promising results were introduced with a class of drugs based on incretins. These drugs were developed as agonists of gastrointestinal peptides in a mono form or a combination of two or three different agonists, achieving results similar to the effects of bariatric surgery. Currently, about 70 different therapeutical principles are in the process of development. Problems related to the drugs on the market are their high prices, limited capacity for production, and lack of experience regarding long-term use.
Keywords: obesity; dietary treatment; exercise; anti-obesity drugs; bariatric surgery; low grade inflammation